Regulation of water regime of sod-podzolic soil in fruit tree nursery and water distribution pattern in the soil profile under different irrigation regimes - A. Yu. Romanovskaya; K. B. Shumakova (Бюллетень Почвенного института им. В.В. Докучаева, 2021)
Based on the results of field experiments carried out in the nursery of Michurin garden of Russian State Agrarian University named after K.A. Timiryazev, rational irrigation schedules for apple-tree seedlings of different age (1-, 2- and 3-year-old) were developed and scientifically substantiated. Excess water was diverted from the experimental plot by underground drainage system, and the drip irrigation system was used for watering plants. With its characteristic low rate of water usage and highly frequent irrigation applications it allows the moisture content to be maintained within a narrow range. The effectiveness of irrigation schedules was evaluated by the response of seedling – their biometric characteristics, determining the productivity of apple trees in orchard in future, such as average plant height, stem diameter at 20 cm height, leaf surface area, which were measured. The amount of high-quality planting stock was recorded in each variant as well. In order to btain 1-year-old apple seedlings it is recommended to maintain soil moisture within the range of 70–90% of field capacity (FC). This irrigation schedule results in the maximum amount of standard planting stock (1-st and 2-nd category) – 25.9 thousand seedlings per ha, with the average leaf surface area of 1 468 cm2, trunk diameter – 1.8 cm, plant height – 140 cm. For 2- and 3-year-old seedlings the differentiated irrigation schedule was developed, whereby the moisture content and depth of the wetted layer varies as the root system grows. In the first year of growth soil moisture should be maintained within the range of 70–90% FC in 0–30 cm layer because of the poorly developed root system; for 2- and 3-year-old nurslings soil moisture can be reduced to 60–80% FC in 0–40 cm and 0–50 cm layer respectively. The height of 2-year-old seedlings was on average 174 cm, leaf surface area – 3 715 cm2, stem diameter at 20 cm height was 2.3 cm, the amount of standard planting stock was 25 thousand seedlings per ha. The 3-year-old seedlings reached the height of 214 cm, were characterized by leaf surface area of 5 973 cm2, stem diameter at 20 cm of 2.8 cm, the yield of standard seedlings was also 25 thousand seedlings per ha. Moreover, for two variants of irrigation (60–80% FC and 70–90% FC) moisture distribution contours immediately after irrigation, 24 hours after irrigation and before the next irrigation application were designed. The areas of segments with different moisture content in vertical section of contours were calculated, thus, revealing the character of moisture distribution down the soil profile and allowing performance of comparative characteristic of irrigation schedules. The obtained wetting contours indicate the absence of unproductive losses of irrigation water for infiltration into the underlying horizons when the considered drip irrigation schedules were applied.